PENERAPAN METODE QUANTUM LEARNING TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR 149 PALEMBANG - Rayvanza Pratama; Muhammad Ari Syawal; Muamar Khadafi; Muhammad Ihsan Sawaluddin; Wira Prasetya Utama; Syarnubi (PAI RAFAH, 2023)
This study aims to examine the application of quantum learning methods to student learning motivation at SD Negeri 149 Palembang. An interview with Mrs. Rosalini, S.Pd., teacher of class VI D, revealed that the applied quantum learning method involves interactive activities such as group discussions and educational games that make students more active and enthusiastic in learning. The interview results show that the mastery of the material by the teacher and the readiness of learning media are the main supporting factors for the effectiveness of this method. The quantum learning method increases students' motivation and participation by creating a fun and contextualized learning environment. However, challenges such as limited resources and variations in students' abilities must be overcome by teacher training, provision of adequate resources, and implementation of differentiated learning strategies. The conclusion of this study is that quantum learning method can significantly increase students' learning motivation with proper support, resulting in better understanding of the material and improving students' social skills.